Molecular tuning of DNA framework–programmed silicification by cationic silica cluster attachment - Xinxin Jing; Haozhi Wang; Jianxiang Huang; Yingying Liu; Zimu Li; Jielin Chen; Yiqun Xu; Lingyun Li; Yunxiao Lin; Damiano Buratto; Qinglin Xia; Muchen Pan; et al. (Proceedings of the National Academy of Sciences, 2026)
The organizational complexity of biominerals has long fascinated scientists seeking to understand biological programming and implement new developments in biomimetic materials chemistry. Nonclassical crystallization pathways have been observed and analyzed in typical crystalline biominerals, such as calcium phosphate, calcium carbonate, and ferric oxide, involving the controlled attachment and reconfiguration of nanoparticles and clusters on organic templates. However, the understanding of templated amorphous silica mineralization remains limited, hindering the rational design of complex silica-based materials. Here, we report the finding of ultrastable and monodispersed cationic silica cluster (CSC) and their assembly using DNA nanostructures as programmable attachment templates. Cryo-EM imaging reveal that a typical CSC with a diameter of gyration of ~3.9 nm and an average molecular weight of ~8, 262 Da is characteristic of a branched hierarchical structure. We demonstrate high-fidelity silicification by tuning the composition and structure of CSC, providing a unified model of silicification by cluster attachment. Our findings pave the way toward the molecular tuning of pre- and postnucleation stages of sol–gel reactions and provide insights for the design of silica-based materials with controlled organization and functionality.